Life Cycle Fluoropolymer Management in Proton Exchange Membrane Electrolysis - Parikhit Sinha; Sabrine M. Cypher (Hydrogen)
Concerns over the life cycle impacts of fluoropolymers have led to their inclusion in broad product restriction proposals for per- and poly-fluorinated alkyl substances (PFAS), despite their non-bioavailable properties and low exposure potential in complex, durable goods such as non-consumer electrical products. Based on the hypothesis that manufacturers are most able to manage the environmental impacts of their products, practical engineering approaches to implementing life cycle fluoropolymer stewardship are evaluated to bridge the ongoing debate between precautionary and risk-based approaches to PFAS management. A life cycle thinking approach is followed that considers product design and alternatives, as well as the product life cycle stages of material sourcing, manufacturing, field deployment, and end-of-life. Over the product life cycle, the material sourcing and end-of-life stages are most impactful in minimizing potential life cycle PFAS emissions. Sourcing fluoropolymers from suppliers with fluorosurfactant emissions control and replacement minimizes the potential emissions of bio-available PFAS substances. A stack-as-service approach to electrolyzer operations ensures a takeback mechanism for the recycling of end-of-life fluoropolymer materials. Retaining electrolytic hydrogen’s license to operate results in over USD 2 of environmental and health benefits per kilogram of hydrogen produced from reduced greenhouse gas and air pollutant emissions compared to conventional hydrogen production via steam methane reforming.